A Three Area Interconnected Power System Network Load Frequency Controller Simulator - Ibrahim Olawale Muritala; M B Mu’azu; E A Adedokun (Universitas Muhammadiyah Malang, 2018)
This paper presents a MATLAB simulator of a three area interconnected power system of Thermal-Gas-Hydro. Nonlinearities intrinsic in the interconnected power system of communication delay, Generation Rate Constraint and Generation Dead Band were measured. Bat Inspired Algorithm was exploited to select the favourable parameters of the Model Predictive Controller and the Super Conducting Magnetic Energy Storage. Model Predictive Controller was the subordinate controller employed to minimalize the Area Control Error, Super Conducting Magnetic Energy Storage was the energy buffer to balance the load demand and the power generated. Integral Time Absolute Error was the performance metrics employed to minimize the Area Control Error. Parametric dissimilarity was tested on the inter-connected power system to observe the efficacy of the controller. Step load perturbation of was concurrently applied to the three-area inter-connected network, was introduced to the thermal generating unit, was introduced to the gas and hydro generating unit. Value of the tie-line was introduced to examine its effect on the frequency deviation. The results performed better when compared with Model Predictive Controller joined with Super Conducting Magnetic Energy Storage against the Model Predictive Controller without Super Conducting Magnetic Energy Storage in relations to settling time, overshoot and undershoot.